Integral representations for binomial sums of chances of winning - Dong, Zhao (Ars mathematica contemporanea, 2017)
Addona, Wagon and Wilf (Ars Math. Contemp. 4 (1) (2011), 29-62) examined a problem about the winning chances in tossing unbalanced coins. Here we present some integral representations associated with such winning probabilities in a more general setting via using certain Fourier transform method. When our newly introduced parameters ?$(r, d)$? are set to be ?$(0, 1)$?, one of our results reduces to the main formula in the above reference.
Keywords: binomska vsota; integralska reprezentacija; neuravnotežen kovanec; verjetnostna analiza